In Search of an Alternative Agricultural Extension Strategy:An Action Research on Off-season Vegetable Production in Nepal - Murari Suvedi; Ramjee P. Ghimire (Journal of International Agricultural and Extension Education, 2016)
Agricultural extension services in Nepal are in serious need of revival. An extension approach that brings agricultural stakeholders together and fosters co-learning among them is paramount for agricultural development. This study, conducted in 2013 in Hamsapur, Nepal, aims to assess the current agricultural extension services and search for an alternative extension strategy for speedy agricultural development. Specifically, the study seeks to examine the current agricultural production patterns; assess farmers’ perceptions of the participatory action research (PAR) approach; and identify barriers for adoption of new agricultural technologies by farmers. Personal interviews and observations were employed for collecting qualitative and quantitative data. Ninety-two farmers participated in the study. Farmers, including women and youths, found off-season tomato production beneficial to them. Marketing of vegetables and lack of irrigation, education and knowledge are problems facing farmers. Farmers are optimistic about increasing farm productivity by adopting new and improved technologies. The PAR approach appears to be effective in helping smallholders when non-governmental organizations, farmers and educational institutions work together. Agricultural programs would likely succeed if there were provision of input such as seeds, fertilizers and farmer-to-farmer extension, and if technologies were market-driven and compatible with target communities.
Keywords: off-season vegetable production; participatory action research; agricultural extension services; Nepal